2015
DOI: 10.1590/1984-70332015v15n3a27
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterosis of relevant fruit traits of tomato genotypes for industrial processing

Abstract: -The objective was to estimate the combining ability of lines and heterosis in industrial tomato

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…These authors recommended the selection of some hybrids for release as commercial cultivars and other hybrids for use as base populations to obtain new elite inbred lines with disease resistance. Figueiredo et al (2015;2016a) worked to improve processing tomatoes and evaluated ten elite lines, their crossings and two processing tomato hybrids for yield and postharvest fruit traits. These authors observed high genetic variability among the inbred lines, experimental hybrids and commercial hybrids and concluded that the best hybrids can be selected for release with the commercial hybrids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors recommended the selection of some hybrids for release as commercial cultivars and other hybrids for use as base populations to obtain new elite inbred lines with disease resistance. Figueiredo et al (2015;2016a) worked to improve processing tomatoes and evaluated ten elite lines, their crossings and two processing tomato hybrids for yield and postharvest fruit traits. These authors observed high genetic variability among the inbred lines, experimental hybrids and commercial hybrids and concluded that the best hybrids can be selected for release with the commercial hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…For VC content, the formation of six groups of genotypes with identical means was observed with the hybrids Granadero, Laura and Red Spring, which belong to the genotype group with the highest averages (Table 3). In the industrialization of tomato pulp, it was necessary to reduce the pH to prevent the proliferation of microorganisms, and an appropriate pH value should be less than 4.5 (Figueiredo et al, 2015;Soares;Rangel, 2012). In this experiment, the hybrid with a lower pH value was Laura, and this hybrid was isolated from other hybrids and had a pH of 4.37 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with Figueiredo et al (2015), the GCA effects make it possible to advise farmers on the selection of the most promising intrapopulation parents for improvement programs. The standard-deviation of the contrasts, together with the GCA estimates, help in this selection, which are considered superior to those parents whose GCA estimates were at least two times greater than the standard-deviations (CRUZ; REGAZZI; CARNEIRO, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, tomato breeders pay more attention towards producing new hybrids to suffice the ever-increasing demands of growers and customers alike. Figueiredo et al (2015) found wide range of heterosis values among different tomato genotypes. Shakil et al (2017) indicated that maximum heterosis (78.11%) for marketable yield of tomato was found in F 1 hybrid resulting from a cross between lines 017856 and Roma.…”
Section: Introductionmentioning
confidence: 86%